The Study on the Active Site Regulated RuOx/Sn0.2Ti0.8O2 Catalysts with Different Ru Precursors for the Catalytic Oxidation of Dichloromethane - Yang Yang (MDPI AG, 2021)
Chlorine-containing volatile organic compounds (CVOCs) present in industrial exhaust gas can cause great harm to the human body and the environment. In order to further study the catalytic oxidation of CVOCs, an active site regulated RuOx/Sn0.2Ti0.8O2 catalyst with different Ru precursors was developed. With Dichloromethane as the model molecule, the activity test results showed that the optimization of Ru precursor using Ru colloid significantly increased the activity of the catalyst (T90 was reduced by about 90 °C when the Ru loading was 1 wt%). The analysis of characterization results showed that the improvement of the catalytic performance was mainly due to the improvement of the active species dispersion (the size of Ru cluster was reduced from 3–4 nm to about 1.3 nm) and the enhancement of the interaction between the active species and the support. The utilization efficiency of the active components was improved by nearly doubling TOF value, and the overall oxidation performance of the catalyst was also enhanced. The relationship between the Ru loading and the catalytic activity of the catalyst was also studied to better determine the optimal Ru loading. It could be found that with the increase in Ru loading, the dispersibility of RuOx species on the catalyst surface gradually decreased, despite the increase in their total amount. The combined influence of these two effects led to little change in the catalytic activity of the catalyst at first, and then a significant increase. Therefore, this research is meaningful for the efficient treatment of CVOCs and further reducing the content of active components in the catalysts.